La autonomía de las confesiones religiosas: Aportes desde el derecho de la Unión Europea - Palomino Lozano, Rafael (Ius canonicum, 2023)
The autonomy of religious groups has recently been questioned in the light of the socalled sexual rights and the requirements of equality and non-discrimination legislation. This situation demands an examination of the meaning, content and rationale of the autonomy of religious groups, analyzing its value in the law of the EU.